The I Ching : A Biography - Smith, Richard J. (Book collections on Project MUSE., 2012)
The I Ching originated in China as a divination manual more than three thousand years ago. In 136 BCE the emperor declared it a Confucian classic, and in the centuries that followed, this work had a profound influence on the philosophy, religion, art, literature, politics, science, technology, and medicine of various cultures throughout East Asia. Jesuit missionaries brought knowledge of the I Ching to Europe in the seventeenth century, and the American counterculture embraced it in the 1960s. Here Richard Smith tells the extraordinary story of how this cryptic and once obscure book became on.